Scaling containers with multicluster GKE and Istio (O'Reilly Media, 2019)
"Containers are all the rage these days, but how do you go from a single sandbox cluster to a globally distributed enterprise-scale architecture. Christopher Grant dives into the options and considerations for managing multiple clusters across regions and data centers, covering both infrastructure and application design best practices, such as hybrid and multicluster configurations as well as decomposing applications into system, service, and microservices."--Resource description page